Educação neoliberal, escolas tecnicistas e ensino de língua inglesa : conexões e tensões - Guimarães, Marianne Vieira (2018)
In the light of critical pedagogy and foreign language education, and through some of its authors such as Freire (1975, 1986, 1991, 1997, 2009, 2011), Giroux (1997), Menezes de Souza (2011), Duboc (2009, 2012), and Ferraz (2012, 2013, 2015), amongst others, this study aims to reflect on the role of school, more specifically on the understanding of teachers and students of one of the federal technological institutes of the state of Espírito Santo (IFES) in relation to the reasons why they teach and study English at times in which neoliberal education is conducive to an imagery that perpetuates the vision of English as a lingua franca, global and hegemonic language. Moreover, as technical education can be considered a ‘product’ which is historically derived from the Industrial Revolution, it shows interest in a school ideologically linked to the needs of the economic market. This fact may spread a discourse that English is the language of the market, without exposing the other perspectives that permeate this discourse. Through interviews and class observation at an IFES campus, we sought to understand the connections and tensions exposed by the participants, and to analyze the institutional documents in order to problematize supposed influences of neoliberal ideals in English language teaching and learning in this Technological Institute. Therefore, we strive to answer some questions: is the English language considered a qualification instrument for the labor market or a language that can collaborate with the education of critical citizens? Could it be both visions? Furthermore, with a qualitative and ethnographic character, and through observation and recording of classes, documental analysis and conversation with students and teachers, this research aims to understand the role of the English language in the technical education of the ES.